THE DISTRIBUTION OF OPTIONAL AND OBLIGATORY PLURAL MORPHEMES: CROSS-LINGUISTIC STUDY OF UZBEK -LAR AND KOREAN - 들 - Abdiraximova Iqboloy O’ktam qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This study compares how Uzbek and Korean express plurality through the suffixes -lar and - 들 . Although both languages are agglutinative and share a subject– object–verb word order, they apply plural marking in different ways. Using 400 noun phrases from the Sejong Corpus (Korean) and the Uzbek National Corpus, we examine how animacy, definiteness, the presence of numerals, and syntactic position influence the use of these suffixes. The results reveal a clear contrast: Uzbek -lar is largely optional and frequently omitted when context or a number word already indicates plurality. In contrast, Korean - 들 is strongly restricted to human and animate referents, systematically avoided with explicit numerals or classifiers, and preferred in formal registers. These findings demonstrate that plural marking in both languages is driven by semantic and pragmatic conditions rather than strict grammatical rules. The study contributes to cross-linguistic research on nominal number, offers practical insights for Uzbek–Korean language teaching, and provides empirically grounded constraints for machine translation and natural language processing systems.